Efek Akar Garcinia rostrata Hassk.ex Hook.f Terhadap Penurunan Kadar Glukosa Darah Mencit Jantan (Mus musculus) Yang Diinduksi Aloksan - Devi Saputri Bahman; Yuliet Yuliet; Ihwan Ihwan (Biocelebes, 2018)
Garcinia rostrata Hassk.ex Hook.f is a plant that empirically used for lowering blood glucose levels. This study aims to determine antidiabetic activity of the n-hexane, ethyl acetate and ethanol-water fractions of its root Garcinia rostrata Hassk.ex Hook.f extract as well as to compare their effects to Glibenclamide as the positive control in alloxan-induced mice. The mice divided into five groups. The first group was given Na.CMC 0.5% (as negative control) and the second one was given Glibenclamide 0.65 mg/kgBW (as positive control), while the other three was given of n-hexane, ethyl acetate and ethanol-water fractions, each at a dose of 130 mg/kgBW. Before given the treatment, the mice was induced by alloxan at a dose of 150 mg/kgBW, by intraperitonial route. At fourth day after induced, the mice its raising blood glucose level >200 mg/dL was given a treatment 25 days by oral route. The level of mice blood glucose was measured 4 times at day 4, 11, 18, and 25, the blood is taken from lateralis vein tail of mice.  Data obtained were statistically analyzed by ANOVA and continued by Duncan test. Based on those results, it can be concluded that the ethanol-water fraction at doses of 130 mg/kgBW has antidiabetic activity in hyperglycemic that is comparable to Glibenclamide. Whereas, ethyl acetate fraction, at dose of 130 mg/kgBW has greater activity in lowering blood glucose level than glibenclamide. Keywords: Garcinia rostrata Hassk.ex Hook.f,  Fraction,  n-hexane,  Ethyl acetate, Ethanol-water, Alloxan.